2005
DOI: 10.1063/1.1899251
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nanoscale C60 field-effect transistors with carbon nanotubes

Abstract: A nanoscale C60 field-effect transistor has been fabricated with carbon nanotubes (C60CNT-FET). A wire of multiwalled carbon nanotube has been anchored by metal pads on a Si wafer, and cut by bombardment with focused Ga2+ ion beam. The cut ends of the wire have been integrated as source-drain electrodes into the C60CNT-FET, with a vacuum evaporated C60 thin film. The C60CNT-FET has exhibited an excellent performance of a low-voltage drive operation, without any short-channel effect even at as small as 100 nm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Apart from metal, FIB can also be used to cut off nanowires for nanogap electrodes. In 2005, Horiuchi et al used a focused Ga ion beam to cut multiwalled carbon nanotubes (MWCNTs) and gap widths of around 50 nm were demonstrated, with which a nanoscale C 60 field‐effect transistor has been constructed . However, the obtained nanogaps are of relatively large sizes and not suitable to connect most organic molecules.…”
Section: Fabrication Of Gated Nanogap Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from metal, FIB can also be used to cut off nanowires for nanogap electrodes. In 2005, Horiuchi et al used a focused Ga ion beam to cut multiwalled carbon nanotubes (MWCNTs) and gap widths of around 50 nm were demonstrated, with which a nanoscale C 60 field‐effect transistor has been constructed . However, the obtained nanogaps are of relatively large sizes and not suitable to connect most organic molecules.…”
Section: Fabrication Of Gated Nanogap Electrodesmentioning
confidence: 99%
“…In addition, compared to bulky metallic electrodes, using few layer graphene can potentially enhance the gating efficiency by shortening the distance between the molecular junction and the gate. Some of the fabrication methods used on metallic electrodes can also be used on carbon‐based materials for nanogap electrodes, such as FIB milling on CNTs for nanogap electrode fabrication, FEB induced sculpture of suspended graphene, and scanning probe based techniques . However, due the unique properties of carbon materials, some methods were specifically developed for carbon material nanogap electrode fabrication.…”
Section: Fabrication Of Gated Nanogap Electrodesmentioning
confidence: 99%
“…5-20 nm) and the proximity effects of a FIB are much less than that of electron beam lithography, a FIB could be a reliable way to prepare nanogap electrodes with the advantages of maskless nanostructuring, good reproducibility, and high speed of the nanogap cutting. Ochiai et al [136] reported that by cutting a wire of a multiwalled carbon nanotube anchored by metal pads on a Si wafer with a focused Ga 2þ ion beam, nanogap electrodes with a separation of approximately 50 nm were obtained. By then integrating the nanogap electrodes as source-drain electrodes with C 60 as a semiconductor, excellent field-effect transistors were achieved.…”
Section: Focused Ion Beam and Oxidative Plasma Ablation For Nanogap Ementioning
confidence: 99%
“…In view of the previous arguments, this system could be regarded as an ideal testbed to investigate TVS. In addition, the employment of CNT electrodes [18][19][20] offers many advantages if compared with usual organic electrodes since they exhibit many advantages in comparison to ordinary metallic contacts: they show higher conductivity, 21 permit better contact to organic molecules, 20 and reduce the screening of the gate electric fields due their smaller size. 19 Furthermore, recent advances in nanofabrication techniques permit a precise control of the gap size in between the CNT leads, 22 which is crucial in the development of single-molecule junctions.…”
Section: Introductionmentioning
confidence: 99%